IMPORT REGULATIONS UNDER CONDITIONS OF ECONOMIC CRISIS - Melnyk, Tetiana (Journal of European Economy, 2017)
The analysis of imports volume and its commodity structure in the major industrial markets of Ukraine in comparison with domestic production revealed that the import supply is not the factor of the domestic producers decline. The recommendations for imports regulation strengthening and macroeconomic policy improvement are substantiated.